Stakeholder influence and local government performance: a systematic literature review - Ricardo Corrêa Gomes; Stephen P. Osborne; Patrícia Guarnieri (Revista de Administração Pública)
Abstract Although stakeholder theory has been on the academic agenda for more than 30 years, empirical evidence is still scant about stakeholders’ influence as determinant factors of local governments’ performance. Evidence from 82 empirical studies on stakeholder influence as a source of local government effectiveness is assessed in this article. The choice of studies was based in a systematic literature review, encompassing articles published in the period from 2007 to 2017 in which stakeholder influences are considered determinant factors of local government performance. This research contributes to this field of knowledge by synthesizing the pertinent publications and pointing out an agenda for future studies.